Association between body roundness index and osteoarthritis: a cross-sectional analysis of NHANES 2011–2018 - Liang, Huazheng; Si, Wenyue; Li, Lin; Yang, Kaiying (Frontiers in Nutrition, 2024)
Objective: The objective of this study was to investigate the potential association between body roundness index (BRI) and the risk of osteoarthritis (OA) in US adults. Methods: A cross-sectional analysis consisting of 20,232 participants was conducted using data from the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2018. Participants (≥20 years of age) were included and divided into OA and non-OA groups. Then, the demographics and characteristics of the participants were compared between the two groups. The relationship between BRI and OA was assessed using a multivariate logistic regression model with fitted smoothed curve techniques. Additionally, subgroup analyses on the correlation between BRI and OA were performed. Results: The BRI scores in OA group were significantly higher than in the non-OA group (6.60 ± 2.62 vs 5.46 ± 2.34, P<0.001). Multivariate logistic analysis revealed that a significantly positive association between BRI and OA (OR = 1.12, 95% CI: 1.09–1.14, P<0.001). In the subgroup analysis, only the race subgroup showed a significant difference between BRI and OA (P<0.001). Conclusions: Our findings highlight a significantly positive association between BRI and OA prevalence in the general US population.